Plastome Rearrangements in the “Adenocalymma-Neojobertia” Clade (Bignonieae, Bignoniaceae) and Its Phylogenetic Implications - Fonseca, Luiz H. M.; Lohmann, Lúcia G. (Frontiers in Plant Science, 2017)
The chloroplast is one of the most important organelles of plants. This organelle has a circular DNA with approximately 130 genes. The use of plastid genomic data in phylogenetic and evolutionary studies became possible with high-throughput sequencing methods, which allowed us to rapidly obtain complete genomes at a reasonable cost. Here, we use high-throughput sequencing to study the “Adenocalymma-Neojobertia” clade (Bignonieae, Bignoniaceae). More specifically, we use Hi-Seq Illumina technology to sequence ten complete plastid genomes. Plastomes were assembled using selected plastid reads and de novo approach with SPAdes. The ten assembled genomes were analyzed in a phylogenetic context using five different partition schemes: (1) 91 protein-coding genes (“coding”); (2) 76 introns and spacers with alignment manually edited (“non-coding edited”); (3) 76 non-coding regions with poorly aligned regions removed using T-Coffee (“non-coding filtered”); (4) 91 coding regions plus 76 non-coding regions edited (“coding + non-coding edited”); and, (5) 91 protein-coding regions plus the 76 filtered non-coding regions (“coding + non-coding filtered”). Fragmented regions were aligned using Mafft. Phylogenetic analyses were conducted using Maximum Likelihood (ML) and Bayesian Criteria (BC). The analyses of the individual plastomes consistently recovered an expansion of the Inverted Repeated (IRs) regions and a compression of the Small Single Copy (SSC) region. Major genomic translocations were observed at the Large Single Copy (LSC) and IRs. ML phylogenetic analyses of the individual datasets led to the same topology, with the exception of the analysis of the “non-coding filtered” dataset. Overall, relationships were strongly supported, with the highest support values obtained through the analysis of the “coding + non-coding edited” dataset. Four regions at the LSC, SSC and IR were selected for primer development. The “Adenocalymma-Neojobertia” clade shows an unusual pattern of plastid structure variation, including four major genomic translocations. These rearrangements challenge the current view of conserved plastid genome architecture in terms of gene order. It also complicates both genomic assemblies using reference genomes and sequence alignments using whole plastomes. Therefore, strategies that employ de novo assemblies and manual evaluation of sequence alignments are required to prevent assembly and alignment errors.